PRELIMINARY FINDINGS OF alpha-ACTININ-3 GENE DISTRIBUTION IN ELITE TURKISH WIND SURFERS - GÜNEY, AHMET İLTER (MACEDONIAN ACAD SCIENCES ARTS, 2013)
A common polymorphism in the alpha-actinin-3 (ACTN3 R577X) gene represents one of the most widely examined variations in terms of performance and genetic predisposition to certain sports. The aim of the present study was to examine the ACTN3 R577X polymorphism in elite Turkish wind surfers. The genotyping procedure was carried out by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Five male and three female wind surfers, eight elite wind surfers in total, were enrolled in the study. Five of the surfers had RX, two had XX and one had RR genotypes. Previous findings indicated that the X allele was the endurance allele. Our findings were in agreement with the previous reports. Seven of our subjects had at least one copy of the X allele that was considered to have a tendency to prolong endurance. Our preliminary results must be supported with further studies in greater numbers of subjects to clarify the effect of gene polymorphism.
Keywords: alpha-Actinin-3 (ACTN3) gene; Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP); Performance; Polymorphism; Sports genetics; ACTN3 R577X POLYMORPHISM; POWER; ASSOCIATION; ENDURANCE; STRENGTH; GENOTYPE; MEN